2022
DOI: 10.3389/fnins.2022.762007
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation Improves Mitochondrial Dysfunction in Post–cardiac Arrest Syndrome in the Asphyxial Cardiac Arrest Model in Rats

Abstract: Cerebral mitochondrial dysfunction during post–cardiac arrest syndrome (PCAS) remains unclear, resulting in a lack of therapeutic options that protect against cerebral ischemia–reperfusion injury. We aimed to assess mitochondrial dysfunction in the hippocampus after cardiac arrest and whether vagus nerve stimulation (VNS) can improve mitochondrial dysfunction and neurological outcomes. In an asphyxial cardiac arrest model, male Sprague–Dawley rats were assigned to the vagus nerve isolation (CA) or VNS (CA + VN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Brain injury after CA is a major cause of poor prognosis in patients. Therefore, the ultimate goal of CPR is the recovery of brain function [31,32]. Previous studies have shown that the dysregulation of TWEAK/Fn14 is associated with the pathophysiology of the neurodegeneration-related disorders [33].…”
Section: Discussionmentioning
confidence: 99%
“…Brain injury after CA is a major cause of poor prognosis in patients. Therefore, the ultimate goal of CPR is the recovery of brain function [31,32]. Previous studies have shown that the dysregulation of TWEAK/Fn14 is associated with the pathophysiology of the neurodegeneration-related disorders [33].…”
Section: Discussionmentioning
confidence: 99%
“…NaHCO3-treated rats showed improved mitochondrial mass and respiration during running exercise [144], and elevated PGC-1α mRNA-the protein product of which is associated with mitochondrial biogenesis-after chronic intense exercise [145]. For its part, iVNS has been shown to have a beneficial effect on cardiac mitochondrial respiration during sepsis [146], post-cardiac arrest syndrome in an asphyxial cardiac arrest model in rats [147], and myocardial ischemia [148]. Furthermore, the protective effect of VNS on myocardial injury during endotoxemia is mediated by a7nAChRs [149,150], identifying mitochondrial respiration as a target of IR activation.…”
Section: Nahco3 and Ir Activators: Metabolic Pathwaysmentioning
confidence: 99%